Work-Life Balance dan Job Hopping pada Generasi Z: Affective Commitment Menjadi Variable Pemediasi - Hafilan Zainul Umam; Praptini Yulianti; Faidal Faidal (Jurnal Ilmu Manajemen, 2026)
This study aims to analyze the effect of work-life balance on job hopping, mediated by affective commitment, among Generation Z in Surabaya. This study employs a quantitative approach using a survey method. The study population consists of Generation Z employees working in Surabaya. The sampling technique used was purposive sampling, with a sample size of 146 respondents. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that work-life balance has a negative and significant effect on job hopping. Additionally, work-life balance has a positive and significant effect on affective commitment. Furthermore, affective commitment has a negative and significant effect on job hopping. The research results also demonstrate that affective commitment mediates the effect of work-life balance on job hopping among Generation Z. These findings are expected to provide theoretical contributions to the development of organizational behavior studies as well as practical contributions to human resource management in retaining young talent in the modern era.